1993
DOI: 10.1209/0295-5075/22/1/002
|View full text |Cite
|
Sign up to set email alerts
|

Driven Tunnelling with Dissipation

Abstract: We study the quantal dynamics of a harmonically driven quartic double well in the presence of dissipation. A master equation for the reduced density operator is derived in the Floquet representation. In the classical limit, this system corresponds to a Duffing oscillator with Ohmic damping. We present numerical results for the transient time evolution and for the stationary sate. The influence of the weak dissipation on interference effects in the context of driven tunnelling is discussed on the basis of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 49 publications
2
72
0
Order By: Relevance
“…It is known [16] that the coherent destruction of tunneling survives to some extent in presence of a coupling to the environment. Certainly, the system will relax in presence of an environment; however, as it is demonstrated in [16], the relaxation process can considerably be slowed down in the presence of a CDT-field.…”
Section: B Freezing the Coherent Dynamics Of A Driven Two-level Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known [16] that the coherent destruction of tunneling survives to some extent in presence of a coupling to the environment. Certainly, the system will relax in presence of an environment; however, as it is demonstrated in [16], the relaxation process can considerably be slowed down in the presence of a CDT-field.…”
Section: B Freezing the Coherent Dynamics Of A Driven Two-level Systemmentioning
confidence: 99%
“…To achieve this goal, various approaches have been undertaken in recent years. (i) It has been shown that the effect of coherent destruction of tunneling (see above) can be used to slow down the relaxation of a quantum system to its asymptotic equilibrium [16]. (ii) Moreover, a suitable tailored sequence of radio-frequency pulses ("quantum bang-bang" [17] or "parity kicks" [18]) that repeatedly flip the state of a two-level atom may be used to suppress decoherence.…”
Section: Introductionmentioning
confidence: 99%
“…In the second case it cannot be treated as a system with proper eigenstates and eigenenergies. A Markovian approach based on a quasienergy spectrum has been implemented in recent work on driven Rydberg atoms [6] and driven dissipative tunneling [7].…”
Section: Introductionmentioning
confidence: 99%
“…Equations (22), (24), consequently allow to express the interaction picture operatorc † 1 (t−τ, t) appearing in the current formula (13) via c α (t), dressed by exponential prefactors. This spectral decomposition allows one to carry out the time and energy integrals in the expression (13) for the net current entering the wire from the left lead.…”
Section: B Floquet Decompositionmentioning
confidence: 99%
“…In the subspace of a single electron, R αβ reduces to the density matrix in the basis of the Floquet states which has been used to describe dissipative driven quantum systems in Refs. 16,18,23,24,25,26. The next step towards the stationary current is to find the Fourier coefficients R αβ,k at asymptotic times.…”
Section: B Floquet Decompositionmentioning
confidence: 99%